2008
DOI: 10.1016/j.bbamem.2008.07.023
|View full text |Cite
|
Sign up to set email alerts
|

NMR investigations of interactions between anesthetics and lipid bilayers

Abstract: Interactions between anesthetics (lidocaine and short chain alcohols) and lipid membranes formed by dimyristoylphosphatidylcholine (DMPC) were studied using NMR spectroscopy. The orientational order of lidocaine was investigated using deuterium NMR on a selectively labelled compound whereas segmental ordering in the lipids was probed by two-dimensional 1H-13C separated local field experiments under magic-angle spinning conditions. In addition, trajectories generated in molecular dynamics (MD) computer simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 72 publications
(102 reference statements)
1
29
0
Order By: Relevance
“…General anesthetic halotane does not show noticeable effect on the order parameters, while hexafluorethane increase the order parameters in saturated lipid chains [23]. Also the previous studies of DMPC membrane in presence of lidocaine showed increase of the order parameters, which was even qualitatively confirmed by the deuterium NMR [27]. Noteworthy, increase of the order parameters not necessarily means decrease of the membrane fluidity, since addition of neutral form of articaine lead to faster diffusion of lipids, as it will be discussed below.…”
Section: Order Parameterssupporting
confidence: 62%
See 1 more Smart Citation
“…General anesthetic halotane does not show noticeable effect on the order parameters, while hexafluorethane increase the order parameters in saturated lipid chains [23]. Also the previous studies of DMPC membrane in presence of lidocaine showed increase of the order parameters, which was even qualitatively confirmed by the deuterium NMR [27]. Noteworthy, increase of the order parameters not necessarily means decrease of the membrane fluidity, since addition of neutral form of articaine lead to faster diffusion of lipids, as it will be discussed below.…”
Section: Order Parameterssupporting
confidence: 62%
“…In recent paper [24] it was demonstrated that addition of local anesthetic benzocaine increases disorder in the membrane. In a series of works [25,26,27], behavior of local anesthetic lidocaine in a model membrane composed of dimyristoylphosphatidylcholine (DMPC, or 14:0/14:0 PC) lipids, as well as changes in the membrane which might be responsible for the anesthetic action were investigated. Among other observations, it was shown [26] that addition of both charged and neutral forms of lidocaine causes noticeable increase of the dipole electrostatic potential in the membrane interior, which may be responsible for blocking of voltage-gated ion channel and thus for the anesthetic action.…”
Section: Introductionmentioning
confidence: 99%
“…This work is aimed at extending such investigations by using for the first time to our knowledge a combination of separated local-field (SLF) NMR spectroscopy (41,(46)(47)(48) and statistical mean-torque theory (35). Studies of natural lipids, as well as natural detergents (49), can benefit from extending methods originally developed for 2 H NMR spectroscopy (50) to cases where 2 H-isotope labeling is impractical.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the lidocaine -membrane (and other anesthetics) interaction perturbs the bilayer structure. It is speculated 175 that this change in the local order will also affect the lipid protein (ion channel) interaction which is claimed to be essential for the anesthetic activity. In paper 179 it was demonstrated that addition of local anesthetic benzocaine increases disorder in the membrane.…”
Section: Anestheticsmentioning
confidence: 99%
“…Another important membrane inclusions can be anesthetics (e.g., lidocaine, benzocaine, halothane, hexafluoroethane, short chain alcohols like methanol, ethanol, 1-alkanols) 105,[173][174][175][176][177][178][179][180] . The specific molecular mechanism of action of anesthetics and details of their interactions with biological membranes are, to a large extent, unknown or poorly understood.…”
Section: Anestheticsmentioning
confidence: 99%